Scaling up Renewable Energy Financing through Islamic Blended Finance: Case Study in Indonesia - Mukhtasor Mukhtasor; Lisa Listiana; Irvan Hermala; Najim Nur Fauziah (International Journal of Energy Economics and Policy, 2023)
This paper outlines to explore the influencing factors of unachieved target of the energy mix from renewable energy (RE) sources in Indonesia, to develop an integrated Islamic blended finance model for financing RE projects in Indonesia, and to analyse the costs and benefits of the proposed model. This research employs an exploratory sequential mixed method with the qualitative phase through in-depth interviews and Focus Group Discussions (FGD) and quantitative phases using primary and secondary data to simulate the Agent-Based Model (ABM) of the proposed model. The paper found three main financing issues on RE sector in Indonesia, including high investment costs and long payback period of RE projects, high risk perception to finance RE projects, and the uncertainty of investment return for RE developers. Besides, based on ABM simulation, Islamic blended finance can contribute to reduce the required period to achieve the energy mix target. Despite the less familiarity of Islamic finance instrument for the RE sector, an initial of a pilot project in place of the proposed business model might increase common awareness regarding this potential. Hence, policy implication delivered in this paper should be a key component to scale up RE sector via Islamic blended finance instrument.